EFEKTIVITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN GLADAGSARI KABUPATEN BOYOLALI - Cinda Khansa Arroiffah; Kushandajani - -; Fitriyah - - (Journal of Politic and Government Studies, 2023)
This research discusses the effectiveness of the District Integrated Administration Service (PATEN) in Gladagsari District after the policy of dividing three districts in Boyolali Regency in 2018. This research uses the theory of service effectiveness in analyzing the effectiveness of the District Integrated Administration Service (PATEN) in Gladagsari District. The method used is a qualitative approach that is descriptive with data collection techniques such as in-depth interviews, documentation studies, and library studies. In-depth interviews in this research were conducted with Head of Gladagsari District, Secretary of Gladagasari District, Head of the Sectional Service of Gladagsari District, PATEN Officer of Gladangsari District, and PATEN applicant community in Gladagsari District. The data obtained is then analyzed using data reduction techniques, data presentation, and conclusion drawing. The results of the research found that Gladagsari District provides licensing services and non-licensing services based on Boyolali Regent Regulation Number 34 of 2014 concerning Delegation of Part of the Regent’s Authority to the Head of District in the Framework of Implementation Integrated District Administrative Services (PATEN) within the Boyolali Regency Government. Based on the data obtained and concluded on each indicator of service effectiveness, namely service time which includes speed and punctuality of service is in accordance with the provisions and standards for estimating service completion. The suitability and accuracy of services are considered effective, although there are things that need to be improved, especially in the disclosure of digital service information. The style of service delivery has implemented an attitude of competence according to applicable standards and values of politeness, as evidenced by the number of people who are satisfied with the attitude and style of service delivery